Nora’s lesion: bizarre parosteal osteochondromatous proliferation in right foot: a case report - Yadav, Shikhar; G., Divya; Mohan, Jithin; Varghese, Joice (International Journal of Research in Orthopaedics, 2021)
Nora’s lesion is a benign lesion involving mainly the proximal phalanges, metatarsals or metacarpals in the hands and feet. It may be easily confused with a malignant entity and was first identified and reported by Nora et al. in 1983. We present a case of a 12 years old female with complains of a swelling over the right foot noticed 4 months ago. Plain radiograph revealed heterotrophic calcification over the dorso-lateral aspect of the head of the first metatarsal. MRI scan of the foot was suggestive of a benign pathology with a differential of bizarre parosteal osteochondromatous proliferation (BPOP) or an osteochondroma. The patient was managed with excision biopsy and lesion was excised along with the pseudo-capsule and adjoining periosteum. Cortex appeared normal and wound was washed with hydrogen peroxide and incision closed. Histopathology report was suggestive of Nora’s lesion. One year follow up of the patient showed no recurrence. BPOP proliferation is a benign lesion however differentials need to be kept in mind and treatment with excision of the lesion along with the pseudo-capsule and periosteal tissue beneath the lesion has low rates of recurrence.